Norse-Icelandic Culture as a Means of Liberation from Industrial Victorian England in William Morris's Works - Vieira, Dienifer Feijó; Soares, Isabelle Maria (Em Tese, 2025)
This article aims to outline the relationship between the English writer William Morris (1834-1896) and the medieval culture, particularly the Norse culture from Icelandic tradition. Morris witnessed the acceleration of the Industrial Revolution in his country and lamented the destruction of British natural landscapes and the impoverishment of human interactions with their own environment. By revisiting and reorganizing stories and motifs from the Middle Ages, a period he admired, Morris sought to critique the modernity of his time. Therefore, this article will delineate Morris’s connections to medieval culture, especially Norse-Icelandic culture, highlighting how this relationship is reflected in his literary works.